Where to "play ball!"? : a case of a minor league baseball team's future - Hyatt, Craig G.; Chard, Chris; Kerwin, Shannon, 1981- (London : Human Kinetics, Inc, 2022)
After 30 years as a minor league baseball team afﬁliated with various Major League Baseball (MLB) teams, the Campton Hills Crushers were left without a league to play in when MLB removed the afﬁliations of 42 former minor league farm teams in the winter of 2020-2021. Team management believed that they had four options for playing baseball in the 2021 season, including joining a well-established independent professional minor league, joining a well-established amateur summer collegiate league, starting their own in-house independent professional minor league with all teams playing out of Crusher Stadium, or starting their own in-house amateur summer collegiate league with all teams playing out of Crusher Stadium. Participants are asked to recommend one of the four scenarios to team management, based on utilizing a decision-making model that incorporates a pro/con analysis.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business enterprises -- Finance -- Case studies; Decision making -- Case studies; Minor league baseball -- Case studies